STANDARISASI SPESIFIK, NON SPESIFIK, DAN SKRINING FITOKIMIA EKSTRAK ETANOL BUAH BELIMBING WULUH (Averrhoa bilimbi L.) - Jasinca Arga Cetta Ramaniya; Adelia Nur Aini Saraswati; Anika Putri Rahmadani; Putri Lana Awallia; Shalsabila Tristananda (Jurnal Farmasi IKIFA, 2025)
The starfruit plant (Averrhoa bilimbi L.) has the potential to be used as traditional medicine. This plant can function as an antilithiasis, antihypercholesterolemia, and antidiabetic agent. To ensure the traditional medicinal plant provides safe, high-quality, and effective benefits, standardization is required. This practicum aims to observe the starfruit and establish the quality parameters of its ethanol extract, both specific and non-specific. The thick extract was obtained through maceration using 96% ethanol as the solvent. Organoleptic observations showed that the thick extract was dark green and had an aromatic smell. The non-specific parameters tested included moisture content using a moisture analyzer, ethanol-soluble extract content, water-soluble extract content, and total ash content. The results of the specific and non-specific parameter standardization of the starfruit extract showed that the drying loss of the simplicia weighed 2.2 grams, with a specific gravity of 0.836 grams/ml, extract moisture content of 17%, ethanol-soluble extract content of 24%, and water-soluble extract content of 56%.